2398. Utilization Practices of Ceftazidime–Avibactam at Academic Medical Centers in the United States. (26th November 2018) - Strich, Jeffrey R; Ricotta, Emily; Lai, Yi Ling; Hohmann, Samuel; Hussain, Sadia; Rhee, Chanu; Klompas, Michael; Palmore, Tara N; III, John H Powers; Dekker, John P; Adjemian, Jennifer; Danner, Robert L; et al.
Abstract: Background: Ceftazidime–avibactam (CAV) was US FDA-approved for complicated intra-abdominal/urinary tract infections in 2015, and for hospital-acquired/ventilator-associated pneumonia in 2018. However, little is known about its real-world use. Methods: Encounters of inpatients receiving CAV at academic hospitals in the Vizient TM Clinical Resource Manager were identified (CAV encounters). CAV administered for ≤2 consecutive days during an encounter or any duration of CAV within 2 days of admission (excluding acute care hospital transfers) was considered empiric therapy. Targeted therapy was defined as ≥4 consecutive days or death within 2 days of therapy; empiric and targeted therapy cohorts were mutually inclusive. CAV-encounter characteristics, use patterns and Infectious Disease (ID) consultation were examined. Quarterly hospital uptake of CAV and % change in CAV encounter prevalence (using Poisson regression) were calculated. Results: From January 2015 to December 2017, 20, 590 CAV doses occurred in 2, 128 encounters among 1, 652 patients. Mean duration of therapy was 8 ± 7.9 days (range 1–86); overall mortality was 24%. The number of hospitals prescribing CAV increased from 5 to 92/168 and quarterly prevalence of CAV encounters increased from 5/10, 000 hospitalizations in 2015q1 to 9.8 in 2017q4 (% change=2.1[0.7–3.6] %/quarter; ( P = 0.004). Therapy was empiric in 904 (42%) encounters and targeted in 1, 472 (69%); 63% of empiric CAV was initiated within 2 days of admission. CAV was initiated in the ICU in 862 (40.5%) encounters. Infection site was coded as respiratory in 34%, urinary in 26% and abdominal in 16% of encounters. Within 31 hospitals reporting consultant specialty, 29% of targeted therapy occurred without ID consultation. For targeted therapy encounters, CAV monotherapy occurred in 841 (57%) and combination therapy in 631 (43%) encounters, which most often included aminoglycosides, colistin or tigecycline. Mortality was 22% in the monotherapy and 25% in the combination therapy group ( P = 0.08). Conclusion: CAV use across US academic medical centers has increased modestly over 3 years. More than 40% of CAV prescriptions appear to be empiric and targeted therapy often occurs without ID consultation at academic centers. Disclosures: All authors: No reported disclosures.